Resistance towards the use of Drama among ESL Lecturers at Institutions of Higher Learning in Kuching / Rebecca Raphael - Raphael, Rebecca (UITM Sarawak,Kampus Samarahan, 2013)
This study aims to investigate a case study on ESL teachers'resistance towards the use of drama in selected institutions of higher learning in Kuching. The benefits that emanate from the use of drama are unquestionable. There are many success stories or researches done that verify the goodness and benefit of drama in ESL classes. However, there are many teachers who are reluctant to use drama as a tool to improve students' communication and enhance their confidence. With that said, this case study is created with three objectives in mind; to find the causes of resistance towards drama, to determine whether teachers' teaching strategies affect their planning of the lessons that cause the resistance and to seek alternatives to drama in the case where teachers totally resist its use. Ten ESL teachers (lecturers) are selected and then interviewed via real-time online interview. Based on the interview, the answers to the three research questions are answered and deeper insights into teachers' point of view are shown. In the final chapter, four categories of teachers are categorised based on their resisting ways; teachers who have used drama and found drama successful and thus continued its usage, teachers who have used drama but found it difficult to be incorporated into the current syllabus and ceased its usage, teachers who have never used drama and would not use it in the future and finally teachers who have never used drama but eventually tried it and continued its usage. Finally, recommendations are then given at the final chapter to assist the four categories of teachers further.